Effects of On-Court Tennis Training Combined with HIIT versus RST on Aerobic Capacity, Speed, Agility, Jumping Ability, and Internal Loads in Young Tennis Players - Morais, J. E. (2025)
The purpose of this study was to compare the effects of on-court tennis training (OTT) combined with high-intensity interval training (HIIT) or repeated sprint training (RST) on the physiological, kinematic, kinetic, and perceptual responses of young tennis players. Twenty-four male tennis players (age 13.6 ± 0.3 years) were randomly assigned to either the OTT + HIIT group (n = 12) or the OTT + RST group (n = 12) three times per week for six weeks. Both groups trained for the same total training time with passive rest in each session. A number of physiological, performance and perceptual responses were measured before and after the 6-week training intervention. All variables showed a significant improvement over time, with maximal oxygen uptake showing the greatest improvement (p < 0.001, η2 = 0.97). The 5-m sprint (p = 0.044, η2 = 0.17), repeated sprint ability (p = 0.021, η2 = 0.22), and T-drill agility (p = 0.048, η2 = 0.17) showed a significant group effect. The OTT + RST group had a lower internal training load (better scores), a lower rate of perceived exertion (better scores), and higher scores in the Physical Activity Enjoyment Scale (PACES) at both times compared to the OTT + HITT group. These results demonstrate that OTT + RST appears to be a more effective training approach to improve speed and agility-based performance responses with more enjoyment in young tennis players.